COMPLICATIONS OF MONKEYPOX: AN INTEGRATIVE REVIEW - Eduarda Almeida de Souza, Cicera; Eduarda das Neves Martins, Fernanda; de Oliveira Cordeiro , Aline; Luíza da Silva Souza, Andréia; Maria Guilherme da Silva Filha, Josefa; Albuquerque Alves, Natan; Walisson de Araujo, Francisco; Camila Rodrigues de Abreu , Maria; Beatriz Alves da Rocha , Camila; Almeida Pinheiro , Milena (Health and Society, 2023)
Introduction: Monkeypox is a rare, viral and emerging disease, although in recent months it has become a growing concern for health professionals and public health authorities around the world. The disease is caused by an orthopoxvirus of the same genus as the human smallpox virus and can cause serious complications in both humans and animals. Objective: To show, through the scientific literature, the complications of monkeypox. Methodology: This is an integrative literature review research, carried out between the months of May and July 2023, through a survey of data in the scientific bases of health: LILACS and SCIELO. Results and Discussion: Through the analysis of the selected studies, the main information for the discussion of this study was evaluated. Scientific evidence has shown that monkeypox complications can vary according to the severity of the patient and can affect different systems of the human body. The scientific literature has pointed out that the main complications of monkeypox include skin infections and skin abscesses. In addition, infection with the virus can provoke the development of cardiac complications, such as myocarditis and heart failure. It can cause abnormal heart rhythms and other cardiovascular problems. Monkeypox develops more severely in people with weakened immune systems because the body has difficulty controlling viral replication. In such cases, the infection can spread quickly and affect various organs and systems in the body. Conclusion: Complications of monkeypox pose significant public health and safety challenges. Although the disease is less lethal than smallpox in humans, it can cause serious complications in infected patients, with localized cutaneous effects such as pustule formation and secondary infections, as well as systemic effects affecting vital organs and body systems.